Hexavalent chromium induced tunable surface functionalization of graphite. Issue 63 (20th June 2016) - Xiang, Bo; Ling, Dong; Gao, Feng; Lou, Han; Gu, Hongbo; Guo, Zhanhu
Abstract : Graphite with the oxygen related functional groups was achieved by functionalized with hexavalent chromium in certain conditions. Abstract : Hexavalent chromium (Cr(vi )) was chosen to serve as an oxidant to functionalize the surface of graphite. The effect of pH and concentration of Cr(vi ) solution on the functionalization of graphite was systematically investigated by Raman spectroscopy, Fourier transform infrared spectroscopy (FT-IR), thermogravimetric analysis (TGA), and X-ray photoelectron spectroscopy (XPS). The results showed that the ether (C–O–C) functional groups were observed on the surface of graphite after being treated with pH = 1.0 solution with a Cr(vi ) concentration of 1000 μg L −1 for 30 min. However, no obvious functional groups were observed on the graphite surface for the pH higher than 2.0 and the Cr(vi ) concentrations higher than 2.0 mg L −1 . The electrical conductivity of functionalized graphite by Cr(vi ) was observed to be good, i.e., the same order of magnitude as that of the as-received graphite without a serious decrease. This work provides a new strategy to functionalize graphite for preparing multifunctional graphite nanocomposites.